A Research on Urban Identity: Sample of Kadikoy District - Begüm Erçevik Sönmez (Alanya Hamdullah Emin Paşa Üniversitesi, 2020)
Cities have idiosyncratic identities composed of the combination of identity elements which are generated by the natural, social or built environments. Due to globalization, neo-liberal approaches and urban branding, cities have lost their unique identities to a significant extent; and resemblances among cities have gradually emerged. Therefore, some research questions occur such as which urban elements are the identity elements that form the unique identity; what are the problems that threaten the identity elements; and which identity features should be emphasized. The aim of this study is to analyze the unique identity and identity elements and also determine the positive and negative identity features of an urban district. Central Kadıköy, located on the Asian side of Istanbul, was chosen as the experiment area and 117 questionnaires were conducted. The results have revealed that the most frequently defined unique identity element of Central Kadıköy is the Bull Statue; the second one is İskele Square and the third one is the Moda Coast. According to the focal points of this study, relation with nature is an important identity feature that needs to be emphasized; on the other hand, over-urbanization and deterioration of historical identity are the characteristics that should be prevented.